Mises and His Understanding of the Capitalist System - Kirzner, Israel M. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
To someone not familiarized with Ludwig von Mises’ understanding of the market, there would appear to be, on the surface of Mises’ exposition, a puzzling tension in it – a tension related to some very basic elements of Mises’ position. We shall find that the resolution of this tension is, once it has been explained, fairly obvious, but we also discover that a careful consideration regarding this resolution can help us to more fully appreciate the uniqueness (and the intellectual integrity) of Mises’ understanding of the capitalist system.